Structural and functional computational analysis of nicotine analogs as potential neuroprotective compounds in Parkinson disease. (June 2020) - Becerra, Gina Paola; Rojas-Rodríguez, Felipe; Ramírez, David; Loaiza, Alix E.; Tobar-Tosse, Fabian; Mejía, Sol M.; González, Janneth
Graphical abstract: Highlights: Geometrical and structural characterization of a new set of eight nicotine analogs is provided. Geometrical conformational analysis over nicotine analogs proved to be a mandatory method for new neuroprotective drug discovery. Two nicotine analogs (A3 and A8) are proposed as potential PD neuroprotective agents. Abstract: As the mechanism of interaction between nicotinic receptors with nicotine analogs is not yet fully understood, information at molecular level obtained from computational calculations is needed. In this sense, this work is a computational study of eight nicotine analogs, all with pyrrolidine ring modifications over a nicotine-based backbone optimized with B3LYP-D3/aug-cc-pVDZ. A molecular characterization was performed focusing on geometrical parameters such as pseudo-rotation angles, atomic charges, HOMO and LUMO orbitals, reactivity indexes and intermolecular interactions. Three analogs, A2 (3-(1, 3-dimethyl-4, 5-dihydro-1h-pirazole-5-yl) pyridine), A3 (3-(3-methyl-4, 5-dihydro-1H-pyrazol-5-yl)-pyridine) and A8 (5-methyl-3-(pyridine-3-yl)-4, 5-dihydroisoxazole), were filtered suggesting putative neuroprotective activity taking into account different reactivity values, such as their lowest hardness: 2.37 eV (A8), 2.43 eV (A2) and 2.56 eV (A3), compared to the highest hardness value found: 2.71 eV for A5 (3-((2S, 4R)-4-(fluoromethyl)-1-methylpyrrolidine-2-il) pyridine), similar to the value of nicotine (2.70 eV). Additionally, molecular docking of all 8 nicotine analogs with the α 7 nicotinic acetylcholine receptor ( α 7 nAChR) was performed. High values of interaction between the receptor and the three nicotine analogs were obtained: A3 (-7.1 kcal/mol), A2 (-6.9 kcal/mol) and A8 (-6.8 kcal/mol); whereas the affinity energy of nicotine was -6.4 kcal/mol. Leu116 and Trp145 are key residues in the binding site of α 7 nAChR interacting with nicotine analogs. Therefore, based upon these results, possible application of these nicotine analogs as neuroprotective compounds and potential implication at the design of novel Parkinson's treatments is evidenced.